253 Identification of transcriptional variants in liver, rumen and jejunum tissue of cattle undergoing compensatory growth. (7th December 2018) - Mullins, Y; Keogh, K; Blackshields, G; Kenny, D; Kelly, A; Waters, S
Abstract: The objective of this study was to identify transcriptional variants in key genes involved in compensatory growth (CG) in cattle. Fifteen Holstein-Friesian bulls were offered a restricted diet (growing at 0.6kg/day) for 125 days (Period 1) followed by ad libitum access to feed for a further 55 days (Period 2), during which they displayed CG. A control group received ad libitum access to feed across both periods. Following 55 days of ad libitum feeding and CG, tissue samples including liver, rumen papillae and jejunal epithelium were sampled from all animals. RNAseq was performed on tissue samples and transcriptional variants were subsequently called from resultant sequencing data as per the GATK guidelines. The Ensembl Variant Effect Predictor program was then used for annotation of identified variants. The bulls displayed CG during Period 2 growing at 1.8 times that rate of the control group. Of the key genes examined (n=53), 1854 transcript variants were identified in cattle undergoing CG. Of the variants identified, 69% were synonymous, 29% were missense, 1% were frameshift variants while 1% were inframe deletions. Four genes contained high impact variants in the liver, namely: CYP51A1, SEMA4B, ACSM1 and ELN . CYP51A1 and SEMA4B which are involved in cholesterol synthesis and receptor activity respectively contained frameshift variants. Two splicing variants were also present in liver; ACSM1, which is involved in GTP binding and ELN which encodes a major structural protein. These same high impact variants were also evident during CG within the rumen; CYP51A1, SEMA4B and ELN and in the jejunum ELN was also classified as a high impact variant. Transcriptional variants identified in the current study may, following validation, may hold potential for use as DNA based biomarkers for the selection of cattle with a superior ability to undergo CG following dietary restriction.